Observing shocks - Pedro Garcia Duarte; Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2011)
Shock is a term of art that pervades modern economics appearing in nearly a quarter of all journal articles in economics and in nearly half in macroeconomics. Surprisingly, its rise as an essential element in the vocabulary of economists can be dated only to the early 1970s. The paper traces the history of shocks in macroeconomics from Frisch and Slutzky in the 1920s and 1930s through real-business-cycle and DSGE models and to the use of shocks as generators of impulse-response functions, which are in turn used as data in matching estimators. The history is organized around the observability of shocks. Aswell as documenting a critical conceptual development in economics, the history of shocks provides a case study that illustrates, but also suggests the limitations of, the distinction drawn by the philosophers of science James Bogen and James Woodward between data and phenomena. The history of shocks shows that this distinction must be substantially relativized if it is to be at all plausible.
Keywords: B22; B23; B41; 330; shock; new classical macroeconomics; real-business-cycle model; Ragnar Frisch; Jan Tinbergen; Robert Lucas; data; phenomena; James Bogen; James Woodward; DSGE model; impulse-response function